SIMILARITIES AND DIFFERENCES OF CASE IN ENGLISH, RUSSIANAND KAZAKH LANGUAGES - Abdibayeva Nadya; Aziz Mukhamadiev (Лучшие интеллектуальные исследования, 2024)
Annotation: The examination of grammatical case in language is a compelling area of study that sheds light on the diverse functions and relationships of nouns and pronouns within sentences. By delving into the concept of case, linguists and language enthusiasts gain valuable insights into the structural nuances that dictate how words interact and convey meaning in communication. The purpose of this article is to investigate the viewpoints of Russian, Kazakh and English academics regarding this linguistic issue. I try to compare and contrast the terminologies and approaches used in each language, studying the relevant theories, using examples from Russian, Kazakh and English literature.